The answer will be as shown in the pic 15x^(2) +35x
![a_n=a_{n-1}+d=a_{n-2}+2d=\cdots=a_1+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da_%7Bn-1%7D%2Bd%3Da_%7Bn-2%7D%2B2d%3D%5Ccdots%3Da_1%2B%28n-1%29d)
which means
![a_{50}=86=a_1+49\times2\implies a_1=-12](https://tex.z-dn.net/?f=a_%7B50%7D%3D86%3Da_1%2B49%5Ctimes2%5Cimplies%20a_1%3D-12)
which in turn means the next two terms are
![a_2=-10](https://tex.z-dn.net/?f=a_2%3D-10)
and
![a_3=-8](https://tex.z-dn.net/?f=a_3%3D-8)
.
Answer:
No the two expressions are not equivalent.
Step-by-step explanation:
the given two expressions t=5 and t=9 are not equivalent because t being a variable cant take two numbers at a same time.however if they are placed in given two expressions of 't' such that that they give equal value when the first expression gives a value 'a' at t=5 while the other expression gives a value 'a' at t=9 then those two expressions will be equal.
Answer: 2t/12
Step-by-step explanation:The quotient of is the result of dividing two terms
The first term is - Twice a number